Oral microbiota and vitamin D impact on oropharyngeal squamous cell carcinogenesis: a narrative literature review. (4th March 2021) - Zanetta, Paola; Squarzanti, Diletta Francesca; Sorrentino, Rita; Rolla, Roberta; Aluffi Valletti, Paolo; Garzaro, Massimiliano; Dell'Era, Valeria; Amoruso, Angela; Azzimonti, Barbara
Abstract: An emerging body of research is revealing the microbiota pivotal involvement in determining the health or disease state of several human niches, and that of vitamin D also in extra-skeletal regions. Nevertheless, much of the oral microbiota and vitamin D reciprocal impact in oropharyngeal squamous cell carcinogenesis (OPSCC) is still mostly unknown. On this premise, starting from an in-depth scientific bibliographic analysis, this narrative literature review aims to show a detailed view of the state of the art on their contribution in the pathogenesis of this cancer type. Significant differences in the oral microbiota species quantity and quality have been detected in OPSCC-affected patients; in particular, mainly high-risk human papillomaviruses (HR-HPVs), Fusobacterium nucleatum, Porphyromonas gingivalis, Pseudomonas aeruginosa, and Candida spp. seem to be highly represented. Vitamin D prevents and fights infections promoted by the above identified pathogens, thus confirming its homeostatic function on the microbiota balance. However, its antimicrobial and antitumoral actions, well-described for the gut, have not been fully documented for the oropharynx yet. Deeper investigations of the mechanisms that link vitamin D levels, oral microbial diversity and inflammatory processes will lead to a better definition of OPSCC risk factors for the optimization of specific prevention and treatment strategies.